Czynniki konkurencyjności wybranych kanałów dystrybucji żywności w opinii konsumentów - Cyrek, Piotr; Cyran, Kazimierz (Factors of Competitiveness of Chosen Food Distribution Channels in Consumers' Opinion, 2006)
One of the elements strengthening competitive advantage of trade enterprises is possession and a continuous improvement in the abilities of diagnosing and meeting purchasing needs of consumers. Purchasing preferences are, however, strongly diversified, especially when the form of assessed distribution channel is taken as a diversifying factor. Many factors decide about the choice of a purchasing place, among others there are: a diversity of assortment, a level of prices, quality of offered products, professionalism and culture of personnel, properly chosen trade time, favorable purchasing climate, a unique offer and some added services. However, the level of relevance of these factors is different for any individual distribution channel.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1118, t. 1, s. 147-152